2019
DOI: 10.21608/rpbs.2019.11644.1029
|View full text |Cite
|
Sign up to set email alerts
|

Review article on Chemical constituents and Biological activity of Thymelaea hirsuta

Abstract: Thymelaea hirsuta a perennial, evergreen and dioecious shrub, which is native to North Africa. T. hirsuta is a widespread invasive weed and is commonly known as "Methnane". Along the history, T. hirsuta, family Thymelaeaceae, has been recognized as an important medicinal plant. Much research has been carried out on the medical applications of Methnane. The choice of the plant was based on the good previous biological study of T. hirsuta plant extract to use as anticancer, hepatoprotective and anti-diapetic. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The number of leukocytes attracted to the air-induced cavity after the carrageenan injection alone was 6 × 10 5 cells/mL higher than the number of leukocytes found in the group treated with the anti-inflammatory drug diclofenac (4.5 × 10 5 cells/mL) or in the group treated with the NPs (3.5 × 10 5 cells/mL), as shown in Figure . , …”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The number of leukocytes attracted to the air-induced cavity after the carrageenan injection alone was 6 × 10 5 cells/mL higher than the number of leukocytes found in the group treated with the anti-inflammatory drug diclofenac (4.5 × 10 5 cells/mL) or in the group treated with the NPs (3.5 × 10 5 cells/mL), as shown in Figure . , …”
Section: Resultsmentioning
confidence: 77%
“…The number of leukocytes attracted to the air-induced cavity after the carrageenan injection alone was 6 × 10 5 cells/mL higher than the number of leukocytes found in the group treated with the anti-inflammatory drug diclofenac (4.5 × 10 5 cells/mL) or in the group treated with the NPs (3.5 × 10 5 cells/mL), as shown in Figure 8. 59,60 Reduction of Adjuvant Arthritis-Induced Paw Edema. Preinjection of CuO-NPs revealed that compared to the control group, it was possible to reduce paw edema in rats by administering the treatment for a total of 21 days.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…(Shao et al, 2013) reported that application of 0.05 g/mL aqueous extract of whole P. harmala plant greatly suppressed growth of wheat and lettuce seedling, indicating the presence of active phytotoxins in this plant. Also, there were significant differences between plant extracts on vegetative growth, where T. hirsute recorded the highest value in most characters, this may be due to T. hirsuta extracts are rich sources of natural antioxidants which appears to be an alternative to synthetic antioxidants which reflected on growth of plants (Amari et al, 2014 andBadawya et al 2019).…”
Section: Effect Of Biofertilizers Treatments and Some Sinai's Flora Extracts On Vegetative Growth Of Faba Bean Plantmentioning
confidence: 96%
“…Additionally, Bedouins have recruited powdered Thymelaea hirsuta in their traditional veterinary medicine to prevent miscarriages in she-camels [ 17 ]. Generally, steroidal compounds, flavonoids, coumarins, and lignans are the active chemical constituents that play a role in biological activity [ 19 ]. The Thymelaea hirsuta aqueous extracts are highly active sources of natural antioxidants, which play an essential role in controlling various pathological conditions, such as Parkinson’s disease and Alzheimer’s disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%